Short-term and Long-term Predicted Outcomes after Swenson’s Pull-through Procedure for Hirschsprung Disease - Aysar Hameed Oraibi; Amier Ejrish Alkafaji; Hayder Neamah Hassan (Medical Journal of Babylon)
Background: Hirschsprung disease (HD) is a congenital deficiency of myenteric and parasympathetic ganglion cells in the last portion of the bowel, resulting in a loss of function and consequently causing intestinal blockage and clinical symptoms of a distended abdomen. Objectives: This study aimed to follow up and investigate the early and late complications of patients diagnosed with HD after definitive surgical treatment by Swenson’s technique. Materials and Methods: A prospective cross-sectional study was conducted on 38 patients ranging from neonates to adolescents, diagnosed with HD and who underwent Swenson’s technique. The initial suspicion of HD by clinical features, and the final diagnosis by rectal and colonic biopsies, and contrast enemas could help in the diagnosis of HD. Postoperative care included short-term and long-term follow-up after Swenson’s pull procedure for HD. The extension of aganglionosis in HD was evaluated to determine the type of HD. Results: The results of this study revealed that 38 patients diagnosed with HD had a male-to-female ratio of 3.2: 1. The larger age group of patients (23, 60.5%) was infants. Constipation, delayed meconium, and abdominal distension were expressed in 23 (60.5%), 15 (39.5%), and 38 (100%) cases, respectively. Short-segment type had a higher frequency of 31 (81.6%). The wound infection formed a major earlier complication in 15 (39.5%) patients. Later complications were postoperative enterocolitis in 14 (36.8%) patients. Constipation represented in 8 (21.1%) patients and fecal incontinence in 7 (18.4%) patients. Perianal excoriation was seen in 19 (50%) patients, 27 (71.1%) patients suffered from abnormal foul-smelling stool odor, and 13 (34.2%) patients had abnormal bowel sounds and abdominal distension. Conclusion: Mostly, HD is diagnosed at an age <1 year, and males are the most predominant sex at diagnosis. Most short-term complications are related to wound infection and pus formation, whereas long-term complications are related to efficiency for good fecal continence, constipation, enterocolitis, and behavioral issues.